Quelles politiques foncières pour le logement dans l’agglomération franco-valdo-genevoise ? - Michèle Tranda-Pittion (Revue de Géographie Alpine)
For decades the trans-frontier conurbation of Geneva has suffered from a recurring housing shortage, and the supply of land has been clearly recognized by local professionals as one of the main factors in a resolution of this problem. The cross-boundary nature of the study area presents a dual interest. On the one hand, the three existing political and administrative systems constitute a relatively diverse range of situations and the complexity of the context - one conurbation, 220 communes, but three states (France, Canton Geneva and Canton Vaud) has led some stakeholders to consider it as a laboratory for experiments in terms of working methods with consultations and research conducted in parallel with the application of different operational approaches. The work discussed concludes by noting some key points that could help integrate land supply into the processes of urban production and with other factors that affect feasibility; its careful coordination with other relevant public policies; the establishment of time frames relevant to different stages of implementation and an approach that connects land policies, urban planning and infrastructure provision within a framework resulting in financial feasibility.